2020
DOI: 10.3390/toxins12020133
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Bacillus thuringiensis Cry1Ia Protein Oligomerization Promoted by Midgut Brush Border Membrane Vesicles of Lepidopteran and Coleopteran Insects, or Cultured Insect Cells

Abstract: Bacillus thuringiensis (Bt) produces insecticidal proteins that are either secreted during the vegetative growth phase or accumulated in the crystal inclusions (Cry proteins) in the stationary phase. Cry1I proteins share the three domain (3D) structure typical of crystal proteins but are secreted to the media early in the stationary growth phase. In the generally accepted mode of action of 3D Cry proteins (sequential binding model), the formation of an oligomer (tetramer) has been described as a major step, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 64 publications
(110 reference statements)
1
11
0
Order By: Relevance
“…As described, a rough but generally accepted insecticidal mechanism of Cry toxins is the sequential binding model or the classic mode of action ( Khorramnejad et al, 2020 ). The sequential binding model comprises a complicated multistep process ( Figure 2 ), emphasizing on the specific binding of Cry toxins to a variety of receptors ( Fu et al, 2018 ).…”
Section: The Insecticidal Mechanisms Of Cry Toxinsmentioning
confidence: 99%
“…As described, a rough but generally accepted insecticidal mechanism of Cry toxins is the sequential binding model or the classic mode of action ( Khorramnejad et al, 2020 ). The sequential binding model comprises a complicated multistep process ( Figure 2 ), emphasizing on the specific binding of Cry toxins to a variety of receptors ( Fu et al, 2018 ).…”
Section: The Insecticidal Mechanisms Of Cry Toxinsmentioning
confidence: 99%
“…The oligomeric structure eventually leads to the lytic pore formation that disrupts the midgut insect cell by osmotic shock. However, oligomerization studies of Cry1Ab and Cry1Ia proteins incubated with lepidopteran and coleopteran BBMV, as well as culture insect cells, showed that Cry1Ia oligomerization may not be a requirement for toxicity [ 179 ]. Besides, the appearance of Cry1Ab oligomers when incubated with coleopteran BBMV could be due to an improper insertion of oligomers into the membrane or the inability to induce the post-pore events in the cells [ 179 ].…”
Section: The Crystal Coleopteran-active Proteinsmentioning
confidence: 99%
“…However, oligomerization studies of Cry1Ab and Cry1Ia proteins incubated with lepidopteran and coleopteran BBMV, as well as culture insect cells, showed that Cry1Ia oligomerization may not be a requirement for toxicity [ 179 ]. Besides, the appearance of Cry1Ab oligomers when incubated with coleopteran BBMV could be due to an improper insertion of oligomers into the membrane or the inability to induce the post-pore events in the cells [ 179 ]. Either way, susceptible insects can withstand minor damage, but greater damage destroys the epithelium of the midgut, leading to a disruption in feeding and subsequent starvation death.…”
Section: The Crystal Coleopteran-active Proteinsmentioning
confidence: 99%
“…In addition, other steps in the mode of action (that comprises protein solubilization, activation, binding, oligomerization, and pore formation) have also been addressed. Examples of these steps include the involvement of a novel trypsin protein for toxin activation in Plutella xylostella, discovered after studying a Cry1Ac resistant strain [9], and the promotion of oligomerization of the activated Cry1Ia with insect brush border midgut vesicles, in vitro [10]. The toxicity-promoting effect of a Bt chitin-binding protein that binds to the insect peritrophic matrix has also been studied [11].…”
mentioning
confidence: 99%